2019
DOI: 10.17969/jimfp.v4i1.10242
|View full text |Cite
|
Sign up to set email alerts
|

Pertumbuhan Tunas Pisang Barangan (Musa Acuminata Colla.) akibat Pemberian Benzyl Amino Purin dan Arang Aktif secara In Vitro.

Abstract: Pertumbuhan Tunas Pisang Barangan Akibat Pemberian Benzyl AminoPurin dan Arang Aktif secara In Vitro Accretion of Barangan Banana Shoot Effect of  (BAP)  and Activated Charcoal Explant by In VitroAbstrak. Banana as a superior product of horticultural crops, has not achieved high productivity and has several obstacles in its multiplication. Tissue culture is one solution to overcome this problem. This study aims to determine the composition of PGRBenzil Amino Purine (BAP) and activated charcoal that are appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…In contrast, the use of single BAP was observed to be resulted in less shoot propagation on Barangan Merah cultivar that giving 6 mg L -1 BAP treatment produced 6 shoots from 3 explants at 9 th week after induction [14]. Different results from the use of a single BAP shown by the study [15] on Barangan Merah cultivar that obtained the highest number of shoots per clump were treated with 5 mg L -1 BAP. Kepok Merah cultivars initiation using 3 mg L -1 BA without auxins produced an average number of6shoots at 20 th week after induction [9].…”
Section: The Average Shoots Number Per Explantmentioning
confidence: 67%
See 1 more Smart Citation
“…In contrast, the use of single BAP was observed to be resulted in less shoot propagation on Barangan Merah cultivar that giving 6 mg L -1 BAP treatment produced 6 shoots from 3 explants at 9 th week after induction [14]. Different results from the use of a single BAP shown by the study [15] on Barangan Merah cultivar that obtained the highest number of shoots per clump were treated with 5 mg L -1 BAP. Kepok Merah cultivars initiation using 3 mg L -1 BA without auxins produced an average number of6shoots at 20 th week after induction [9].…”
Section: The Average Shoots Number Per Explantmentioning
confidence: 67%
“…The formation of MBC is controlled or regulated by internal factors (in organisms) and external (environment). Determination of growth regulators triggers agents or substances to start biochemical processes that ultimately lead to growth [15]. Another study with different cultivars and different concentrations of cytokinin showed different results.…”
Section: The Number Percentage and Average Age Of Explants Formed Mul...mentioning
confidence: 99%
“…Tahapan dari penelitian yaitu pembuatan media yang akan digunakan adalah dengan komposisi MS + 2 ppm BAP, setiap botol kultur berisi 30 ml media. Bonggol pisang terlebih dahulu dicuci dengan air mengalir, kupas eksplan hingga ukuran berkisar 5 cm (Saputri et al, 2019).…”
Section: Tahap Pelaksanaanunclassified
“…Media steril jika terlalu lama disimpan pada tempat lembab dan kotor dapat terkontaminasi meskipun belum digunakan, itu terjadi akibat tingginya tingkat populasi inokulum mikro organisme di udara yang lembab maupun suhu terlalu tinggi (Saepudin et al, 2020). Semakin kaya akan nutrisi maka semakin tinggi tingkat kontaminasi suatu media (Saputri et al, 2019). Selain faktor eksternal, terdapat faktor internal penyebab kontaminasi, yaitu dari dalam jaringan eksplan yang dapat terjadi akibat prosedur sterilisasi eksplan kurang baik.…”
Section: Pendahuluanunclassified